Untersuchungen zur Erhöhung der Prozessrobustheit bei der Innenhochdruck-Umformung von flächigen Halbzeugen mit vor- bzw. nachgeschalteten Laserstrahlfügeoperationen - Blankl, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2009)
The scope of this work was the generation of fundamental basics to design robust process chains under the participation of hydroforming and laser processing steps to manufacture high quality sheet metal parts in a low and middle volume production. Therefore a suitable process chain was determined and investigated with Failure Method and Effect Analysis (FMEA) in order to increase the process robustness. The detected weak spots were investigated more closely and suitable strategies to increase the robustness of the whole process chain were determined. In particular results of basic investigations of leakage phenomena in double sheet hydroforming are presented. Furthermore several strategies for laser welding contaminated sheets in overlap configuration are discussed and compared to each other on the basis of experimental results. Finally a new method for designing laser annealing processes is presented and verified on experimental investigations of laser welded dual phase steel sheet